Coining the attributes of nano to micro dual hybrid silica-ceramic waste filler based green HNBR composites for triple percolation: Mechanical properties, thermal, and electrical conductivity - Debabrata Ganguly; Abhijit Bera; Roumita Hore; Sipra Khanra; Pradip K Maji; Dinesh Kumar Kotnees; Santanu Chattopadhyay (Chemical Engineering Journal Advances, 2022)
Industrial waste management and pollution control are the prime concerns today. Ceramic materials are widely used in various industries and applications; therefore, waste generation is enormous. Thus, in this work, we intend to develop silica-ceramic waste-based nano to micro-hybrid filler sustainable composites based on the percolation optimization of mechanical, thermal, and electrical properties. The developed composites exhibited improved mechanical properties and enhanced thermal conductivity (0.8 W/mK) without any surface modification. The reported value of thermal conductivity is almost double with respect to conventional carbon black filled samples (0.43 W/mK). The addition of such hybrid fillers helped in the in-situ modification of the filler network by infringement of the silica network. The composites retained their basic technical properties (tensile strength and elongation at break) even with higher loading of ceramic waste fillers. The system displayed enhanced dispersion due to the incorporation of such exclusive dual hybrid fillers. Such high loading of ceramic fillers without surface treatment or coupling agent is the first of its kind to be reported. The development of the thermal conductivity of the composites was also cross-validated using mathematical models. These composites also possess electrical conductivity in the insulative to semi-conductive domain range. These fillers can find their potential application in new-generation green and environment-friendly fillers to replace carbon black without hampering basic technical properties by reducing the carbon footprints. Due to such a combination of mechanical, electrical, and thermal attributes, these composites can find budding applications in printed circuit boards, mounts, isolators, and other e-automotive applications.